2011
DOI: 10.1073/pnas.1101368108
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of the maize subgenomes by genome dominance and both ancient and ongoing gene loss

Abstract: Ancient tetraploidies are found throughout the eukaryotes. After duplication, one copy of each duplicate gene pair tends to be lost (fractionate). For all studied tetraploidies, the loss of duplicated genes, known as homeologs, homoeologs, ohnologs, or syntenic paralogs, is uneven between duplicate regions. In maize, a species that experienced a tetraploidy 5-12 million years ago, we show that in addition to uneven ancient gene loss, the two complete genomes contained within maize are differentiated by ongoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
749
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 637 publications
(794 citation statements)
references
References 45 publications
41
749
4
Order By: Relevance
“…Most (65.4%) of the genes included in the Musa a/b ancestral blocks are singletons and only 10% are retained in four copies, in agreement with the loss of most gene-duplicated copies after WGD 22 . The most retained gene ontology categories corresponded to genes involved in transcription regulation (transcription factor activity), signal transduction including small GTPase-mediated signal transduction and protein kinases, and translational elongation (Supplementary Text and Supplementary Tables 12-14).…”
Section: Research Lettersupporting
confidence: 59%
“…Most (65.4%) of the genes included in the Musa a/b ancestral blocks are singletons and only 10% are retained in four copies, in agreement with the loss of most gene-duplicated copies after WGD 22 . The most retained gene ontology categories corresponded to genes involved in transcription regulation (transcription factor activity), signal transduction including small GTPase-mediated signal transduction and protein kinases, and translational elongation (Supplementary Text and Supplementary Tables 12-14).…”
Section: Research Lettersupporting
confidence: 59%
“…The rest of the syntenic gene pairs that showed non-dominance were classified as neutral genes. To test whether the occurrences of BjuA dominant gene pairs and the occurrences of BjuB dominant gene pairs are equal, we performed double-side binomial tests on dominant gene pairs for all samples 64 (Supplementary Table 27a,b). Additional details are available in the Supplementary Note.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work showed that gene loss is biased towards one of the parental genomes 3,16 , but our new assembly and annotation instead suggest that 56% of syntenic sorghum orthologues map uniquely to the dominant maize subgenome (designated A, total size 1.16 Gb), whereas only 24% map uniquely to subgenome B (total size 0.63 Gb). Gene loss in maize has primarily been considered in the context of polyploidy and func tional redundancy 16 , but we found that despite its polyploidy, maize has lost a larger proportion (14%) of the 22,048 ancestral gene orthologues than any of the other four grass species evaluated to date (Sorghum, rice, Brachypodium distachyon and Setaria italica; Extended Data Fig. 6).…”
Section: Openmentioning
confidence: 86%